Interfaces of violence with and nursing education: a possible and necessary dialogue - Elisangela Argenta Zanatta; Thais Cristina Hermes; Jean Henrique Krüger; Peterson Luiz Duarte; Carine Vendruscolo (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To identify the professors' ideals and practices of undergraduate nursing education regarding the presence of violence during the teaching-learning process. Methods: Qualitative, descriptive and exploratory research, performed by 19 professors. For the collection of the information it had been used the Creativity and Sensitivity Dynamics. The data had been analyzed establishing its approximation with the referential present in Paulo Freire's works. Results: Violence is, on the theoretical and practical classes, problematized in an elementary way. The professors' actions are influenced by their experiences, however with a superficial critical reflection about practicing. Conclusion: The research reaffirm the need of investments in undergraduate nursing courses, mainly when dealing with issues such as violence, involving dialogue and attitudes based on lovingness enabling affective bonds and encouraging everyone to express themselves.